Distance education in New Zealand: An historical sketch - Don Bewley (Flexible Learning Association of New Zealand, 2012)
Some problems in sketching a history for such a wide-ranging array of New Zealand distance education provider and support agencies are reviewed and the principal agencies tabulated. The coincidence of first school teaching by correspondence and the start of public radio gives a starting point. The narrative suggests how New Zealand distance education expanded, how it achieved a positive identity at home and internationally, and how its various participants found a common framework in DEANZ.